High strength binding of P815 mastocytoma cells is not necessary for their lysis by macrophages which have been primed and triggered in vitro. - Lu, C; Lombardi, M; Shea, C; Dustin, L (1988)
We have examined the hypothesis that binding of P815 mastocytoma cells is a necessary step in lysis of these cells by macrophages which are both "primed" and "triggered" in vitro, Macrophages "primed" by conditioned media containing IFN-gamma, or by rIFN-gamma have an increased ability to bind P815. However, adding either heat-killed Listeria or endotoxin to trigger the primed macrophages has opposite effects on lysis and binding of P815. Lysis is increased. Binding is dramatically decreased. This is true when centrifugal forces of 200 x g, 400 x g, and 800 x g are used to disrupt P815-macrophage binding. Although 100% of P815 cells bound by cytotoxic macrophages are lysed, a large additional population of unbound P815 is also lysed. Detailed kinetic studies indicate that macrophages do not rapidly bind and lyse several cycles of P815. There is an initial lag period of 4 to 6 h before P815 lysis can be detected, and completion of lytic events then occurs within 12 to 14 h. Lysis of P815 bound to cytotoxic macrophages is slightly slower than lysis of the total population of bound and unbound P815. In contrast, D3.1, a cloned CD4+ T cell line, is tightly bound to macrophages but not lysed efficiently. When macrophages are simultaneously confronted with P815 and macrophage-bound D3.1, only the former are lysed. Altogether, the data indicate that P815-macrophage binding, as operationally defined by our assay, is not a necessary step for lysis. These results, by use of macrophages primed and triggered in vitro, are in contrast to previously reported experiments examining P815 binding and lysis by macrophages activated in vivo by infection with bacillus Calmette-Guérin.